Transforming food systems through risk-contingent credit in rural Africa: Development, experimentation, and evaluation - Shee, Apurba; Ndegwa, Michael; Turvey, Calum G.; You, Liangzhi (International Food Policy Research Institute, 2023)
Throughout Africa, climate change is posing severe challenges to agricultural production and food security. Agricultural risks—particularly those associated with drought—are a major cause of low agricultural productivity in most African countries, including Kenya. According to the Government of Kenya, four consecutive years (2008–2011) of drought caused US$12.1 billion in losses, accounting for about 8 percent of GDP, including losses in assets and disruptions to the economy across sectors (Kenya, Ministry of Agriculture, Livestock and Fisheries 2014). Currently, Kenya is in the middle of an acute drought following three consecutive poor rainy seasons. This has led to a drop in crop production nationally of about 70 percent, which has disproportionately exposed the communities of arid and semi-arid lands to hunger and malnutrition.